STUDI ADAPTASI DAN KINERJA PERTUMBUHAN CENDANA (SANTALUM ALBUM L) PADA UMUR 11 TAHUN DI WATUSIPAT KABUPATEN GUNUNG KIDUL - Yayan Hidayan; Yuliah Yuliah (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2017)
Sandalwood (Santalum album L) is a high-value economic tree species that is increasingly threatened and rare in the its natural distribution area. Efforts to save these species through ex-situ conservation have been done by various parties. One of the conservation activities was carried out by BBP-BPTH in 2005 by collecting genetic material from several natural populations at NTT Province. The purpose of this study is to see the growth performance of Cendana plants from 4 provenance of the age of 11 years in Gunung Kidul Regency. Measurements were performed on the total height variable of the tree, the height of the bole length and the stem diameter. The result of data analysis shows that there is significantly different from the population tested for the variable height of tree and the diameter of the stem, while for the bole length is not. The best performance of growth are from the Rote provenance (height is 6.07 m and diameter of stem is 5.08 cm). As for the best adaptation ability is from Rote (92.19%).Key words : Adaptability, conservation, growth, sandalwood